The Pursuit of Meaningful Work: Exploring the Role of Work-Life Balance and Motivation Among Single Women Professionals in South Jakarta - Asrini Mahdia (PT. Hasba Edukasi Mandiri, 2026)
This study aims to determine the influence of work-life balance and work motivation on meaning of work among single women in their 30s and 40s working in multinational Public Relations (PR) agencies in South Jakarta. Meaning of work refers to the degree to which individuals perceive their work as significant, purposeful, and contributing to a greater good. The participants were 20 single women aged 30–49 who had been employed for over one year, selected through purposive sampling. A quantitative correlational approach was employed using Likert-scale questionnaires. Pearson correlation and multiple regression analysis revealed that both work-life balance and work motivation were positively and significantly correlated with meaning of work. These findings suggest that a better balance between work and personal life and stronger work motivation contribute to a deeper sense of meaning in work for single women navigating demanding professional environments during a critical life stage.